The effect of the 'Nemes' training system on leg power. - Hennesy, L. (2002)
Two groups of elite sport players completed a 12 day programme of strength and power training. Both groups completed a standard strength training programme using 3 sets x 8-10 repetitions (reps) on 6-8 exercises for 6 units. In addition the Experimental (E) group completed an individualised mechanical vibration programme using the Nemes system. This consisted of 9 units of training ranging from 4 reps at 40 seconds to 6 reps of 60 seconds for each player. The Control (C) group did not complete an individualised mechanical vibration programme. Physical performance tests were completed on day 1 and day 12. Tests completed included body composition, countermovement jump (CMJ), squat jump (SJ), 30 second Rebound test (30R) and 10 repetitions of leg press using a 10RM load (LP).